Purchasing decision behavior of kudus residents on amanda brownies - Firda, Shynes; Lusianti, Dina; Faidah, Faridhatun (SHM Publisher, 2023)
This study aims to analyze the effect of brand image, price perception, and product quality on purchasing decisions for Amanda Brownies Kudus products. The problem in this study is that there was a decrease in the percentage of the top brand index value for the branded brownies category carried out by the frontier consulting agency, price perception by consumers who judge Amanda's brownies to be more expensive than another competitor. Several consumer reviews state that the quality of brownie products is still lacking. The sample in this study amounted to 110 respondents, using a purposive sampling technique. This study uses multiple linear regression analysis. The results of this study indicated that brand image has a positive and significant effect on purchasing decisions, price perceptions have a negative and insignificant effect on purchasing decisions, and product quality has a positive and significant effect on purchasing decisions. Brand image, price perception, and product quality positively and significantly affect purchasing decisions.